Effects of human development, primary care coverage and the COVID-19 pandemic on the fertility rate among adolescents in Brazil in the period 2012–2021 - Rosa Maria Soares Madeira Domingues; Rafael Sant´Ana Herzog; Marcos Augusto Bastos Dias; Rossana Pulcineli Vieira Francisco; Agatha Sacramento Rodrigues (PLoS ONE, 2025)
The high fertility rate (FR) in adolescents is a global public health problem, with the Americas region having the second highest FR in the world. This study aims to carry out a temporal and spatial analysis of the FR in adolescents in Brazil in the period 2012−2021 and evaluate the effects of primary care population (PCP) coverage on the FR in adolescents in different contexts of human development, measured by the Municipal Human Development Index (HDI-M). This is an ecological study developed in three stages: 1) time trend analysis of the FR in girls aged 10–14 years and 15–19 years; 2) spatial analysis of the FR in girls aged 10–14 years and 15–19 years; and 3) analysis of the effect of PCP coverage on the FR in girls aged 10–19 years in different contexts of HDI-M, before and during the COVID-19 pandemic. In the period from 2012 to 2021, FR for girls aged 10–14 and 15–19 years had a statistically significant decrease, going from 3.4 to 2.4 and from 61.9 to 45.3 per 1,000, respectively. In the year 2021, the downward trend attenuated for girls aged 15–19 years and stopped for girls aged 10–14 years. Clusters with high FR were observed in the North and Midwest regions of the country. Higher FR were observed in municipalities with lower HDI-M and lower PCP coverage, with the increase in PCP coverage having a more intense effect on reducing the FR in municipalities with lower HDI-M. There was an attenuation of the effect of the increase in PCP coverage in the FR during the pandemic period, reinforcing the importance of guaranteeing access to sexual and reproductive health services even in contexts of health crisis.